Unbalanced Data Classification using Feature Selection through BitApriori Algorithm. - Barot, Pratik A; Jethva, H B (International Journal of Computer Sciences and Engineering, 2025)
Frequent pattern mining is used to derive association rules. Association rules specify relativity of target class with rest of the feature(s). The Apriori and FP-growth algorithms are the most famous algorithms used for frequent pattern mining. Classification with feature selection approach is also widely used. This paper provides a detailed study of frequent pattern mining using BitApriori algorithm and use mined association rules for performance improvement of unbalanced data classification. We present a model called FPCM which first mine association rules. Mined association rules are than used for features selection. In final phase, selected features are used in unbalanced data classification using decision tree classifier. Our model shows improved accuracy as compare to the past studies